DESCRIPTION OF DIPLOID SPECIES OF TRIPSACUM IN MEXICO T MAIZAR AND T ZOPILOTENSE SPP NOV - RANDOLPH, LF; HERNANDEZ XOLOCOTZI, EFRAIN (Instituto Nacional de Nutrición, CD MEXICO, DF, MEX, 1949)
Pulque is the product of the fermentation of the juice of Agave atrovirens or A americana The literature concerning its microbiology is reviewed, with a bibliography of 30 titles The action of a strain of Lactobacillus found by the author in 1946 is di
PHYS REV B
Keywords: DESCRIPTION, DIPLOID SPECIES, TRIPSACUM, MEXICO, T MAIZAR, T ZOPILOTENSE, SPP NOV; CIENCIAS DE LA VIDA; BIOLOGIA VEGETAL; BOTANICA GENERAL